2009
DOI: 10.3201/eid1502.081247
|View full text |Cite
|
Sign up to set email alerts
|

Natural Transmission of ZoonoticBabesiaspp. byIxodes ricinusTicks

Abstract: To determine characteristics of natural transmission of Babesia sp. EU1 and B. divergens by adult Ixodes ricinus ticks, we examined tick salivary gland contents. We found that I. ricinus is a competent vector for EU1 and that their sporozoites directly invade erythrocytes. We conclude that EU1 is naturally transmitted by I. ricinus. Ixodes ricinus is a ubiquitous triphasic tick found commonly in Europe. This arthropod feeds on a wide variety of vertebrate hosts, including small rodents and wild and domestic un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 14 publications
(14 reference statements)
1
30
0
1
Order By: Relevance
“…EU1 was the only species found in both feeding and questing I. ricinus, despite the high number of ticks that were screened and the selection of farms located in a region previously identified as endemic for B. divergens. The same finding was previously described by Becker et al (2009), who found no evidence for B. divergens sporozoites in engorged adult or unfed I. ricinus ticks. Cattle and deer are the main hosts of adult I. ricinus ticks and are potential carriers of B. divergens.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…EU1 was the only species found in both feeding and questing I. ricinus, despite the high number of ticks that were screened and the selection of farms located in a region previously identified as endemic for B. divergens. The same finding was previously described by Becker et al (2009), who found no evidence for B. divergens sporozoites in engorged adult or unfed I. ricinus ticks. Cattle and deer are the main hosts of adult I. ricinus ticks and are potential carriers of B. divergens.…”
Section: Discussionsupporting
confidence: 78%
“…and bacteria within the genus Anaplasma, respectively. Ixodes ricinus, the most prevalent tick species in northern and western Europe, is an important vector of both these pathogens (Baumgarten et al 1999;Becker et al 2009;Bonnet et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…This tick has also been shown to be a competent vector for Babesia sp. strain EU-1 (7,9). Roe deer appear to be the wild reservoir host for EU-1, but other reservoir hosts may exist that have not been identified (10).…”
Section: Routes Of Transmissionmentioning
confidence: 99%
“…EU1 were not isolated, despite the use of conditions known to be favorable to their growth from animal blood samples [9,10,13,30]. They share the same tick vector, I. ricinus [31][32][33], and the absence of these three Babesia species in the study region may be explained by the absence or very low abundance of this tick species in these regions [34]. However, we report here the isolation and characterization of a new Babesia from two geographically distant herds in Spain.…”
Section: Discussionmentioning
confidence: 99%